Trefoil factor-3 (TFF3) stimulates de novo angiogenesis in mammary carcinoma both directly and indirectly via IL-8/CXCR2 - Lau W.-H. (Public Library of Science (PLoS), 2018)
10.1371/journal.pone.0141947